EVALUATION OF THE ANTIRADICAL PROPERTIES OF ARCTIUM LAPPA OIL VIA THE DPPH ASSAY METHOD - Ibrohim Asqarov; Azizbek Khojikulov; Gavharoy Akhmadjonova (Web of Journals Publishing, 2025)
The article is devoted to the evaluation of the antioxidant properties of the oil of the Arctium Lappa plant and its antiradical properties using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. In the article, the main active components of the oil of the Arctium plant, such as phytochemical compounds, essential oils and antioxidants, were studied. The radical absorption capacity of the vegetable oil and its antioxidant properties were evaluated using the DPPH method. The results of the study indicate that Arctium oil has high antiradical activity, and at the same time, it has a beneficial potential for health as a natural antioxidant.
Keywords: Antiradicality, oil, DPPH-method, fatty acids, minerals, polyphenols, spectrophotometer, purple colour, sample, research, antioxidant, extract, experiment.